Monitoring of Large Seepage Discharge in Long-Distance Levee Drainage Ditches Based on Water Level Recognition by UAVs - ZHOU Yujie; YAN Jian; WU Xiaoya; LIU Hui; WANG Ting; HUANG Yaoying (Renmin Zhujiang)
In response to the drawbacks of existing monitoring methods for levee drainage ditches with discharge rates exceeding 300 L/s, such as being time-consuming, labor-intensive, or costly, a monitoring method for large seepage discharge in long-distance levee drainage ditches based on image recognition of unmanned aerial vehicles (UAVs) was proposed. This method reviewed the geometric parameters of the monitoring sections of the drainage ditch, calibrated the Manning formula's roughness coefficient, and quickly identified the water depth at each monitoring section by combining the water gauge images collected by UAVs at the monitoring sections and image processing techniques, thereby obtaining the seepage discharge at the monitoring sections and achieving efficient monitoring of the seepage discharge in the levee drainage ditch. Engineering case analysis shows that this method can quickly obtain the seepage discharge of the monitoring section based on UAV-acquired water gauge images of the drainage ditch by reviewing the monitoring section dimensions and calibrating the Manning formula's coefficients. The error between the monitored seepage discharge and the seepage discharge measured using the current meter method is between 5% and 7%.